A new species of Boehlkea (Characiformes: Characidae: Stevardiinae) from the rio Japura, Amazon basin, Brazil - Soares, Isabel M. [UNESP]; Bertaco, Vinicius A.; Ito, Priscila Madoka M.; Zuanon, Jansen (Soc Brasileira Ictiologia, 2017)
A new species of Boehlkea is described from rio Japura, Amazon basin. The new species differs from B. fredcochui by the presence of a vertically elongate humeral spot (vs. absence), complete lateral line (vs. incomplete), four rows of scales below lateral line (vs. three), and lower number of branched anal-fin rays (17-21 vs. 22-25), and from B. orcesi by the higher number of maxillary teeth (13-14 vs. 5-12), greater head length (27.9-29.9% vs. 24.3-27.5% of SL), and by the color pattern (basal half of dorsal-fin, distal portion of pelvic-fin, lower caudal-fin lobe and anal-fin with black chromatophores vs. absence of black chromatophores in the fins).
Keywords: Characidae Clade A; Color pattern; Hemibrycon; Lateral line length; Taxonomy